2016
DOI: 10.1080/13102818.2016.1154803
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of inhomogeneous–anisotropic models of human cortical bone: a tibia study using the finite element method

Abstract: Cortical bone is an inhomogeneous and anisotropic tissue subjected to large loads during typical daily activities. While studies assuming isotropic material properties are frequent, anisotropy and inhomogeneity of cortical bone have been rarely taken into account. Moreover, the question, whether an assumption of anisotropy and inhomogeneity has an impact in the mechanical analysis of cortical bone, has not been explored in the literature. This study explores the relevance of anisotropy in human cortical bone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The inhomogeneous sacral model used in this study can improve the accuracy of FEA. Ahmet et al previously explored the correlation between bone inhomogeneity and reported that inhomogeneous bones can lead to significant differences in stress values compared to rigid bones ( Ün and Çalık, 2016 ). We designed three screw-fixation methods—BMD screw, long screw, and short screw—and by comparing the results of FEA and sacral BMD distribution, we found that the BMD screw had a more reasonable stress distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The inhomogeneous sacral model used in this study can improve the accuracy of FEA. Ahmet et al previously explored the correlation between bone inhomogeneity and reported that inhomogeneous bones can lead to significant differences in stress values compared to rigid bones ( Ün and Çalık, 2016 ). We designed three screw-fixation methods—BMD screw, long screw, and short screw—and by comparing the results of FEA and sacral BMD distribution, we found that the BMD screw had a more reasonable stress distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The inhomogeneous tibia model adopted in this study could improve the accuracy of the FEA. Ahmet et al explored the relevance of inhomogeneity in the tibia and reported that the inhomogeneous tibia would cause a substantial difference in the stress values compared with the rigid one ( Venäläinen et al, 2016 ; Ün and Çalık, 2016 ). On the other hand, choosing an appropriate method to acquire the load is essential for the FEA.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the analysis depends on the veracity of the model. In this study, a non-homogeneous 3D tibia model was used, which means that it will be closer to real human bone than a homogeneous bone model, making the results of the study more realistic (Venalainen et al, 2016;Ün and Çalık, 2016). According to Ruggiero et al (2019) we can learn that the quality of the hexahedral mesh is better than that of the tetrahedral one, especially in the dynamic condition.…”
Section: Discussionmentioning
confidence: 99%